2021
DOI: 10.1007/s00604-021-04979-8
|View full text |Cite
|
Sign up to set email alerts
|

Dual-modality loop-mediated isothermal amplification for pretreatment-free detection of Septin9 methylated DNA in colorectal cancer

Abstract: Currently, the determination of DNA methylation is still a challenge due to the limited efficiency of enrichment, bisulfite modification, and detection. In this study, a dual-modality loop-mediated isothermal amplification integrated with magnetic bead isolation is proposed for the determination of methylated Septin9 gene in colorectal cancer. Magnetic beads modified with anti-methyl cytosine antibody were prepared for fast enrichment of methylated DNA through specific immunoaffinity (30 min). One-pot real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In addition to the inherent magnetic force, superparamagnetic nanoparticles can also improve the analytical signal due to the oxidation/reduction processes, which can decrease the signal-to-noise ratio. Lin et al fabricated a magnetic bead-based optical sensor with low detection limits (0.02 ng/µL) using HCT 116 cells [ 39 ]. Recently, Syedmoradi et al reported an electrochemical system using SPCE electrodes that achieved a good linear range with a detection limit of 0.01 pM [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the inherent magnetic force, superparamagnetic nanoparticles can also improve the analytical signal due to the oxidation/reduction processes, which can decrease the signal-to-noise ratio. Lin et al fabricated a magnetic bead-based optical sensor with low detection limits (0.02 ng/µL) using HCT 116 cells [ 39 ]. Recently, Syedmoradi et al reported an electrochemical system using SPCE electrodes that achieved a good linear range with a detection limit of 0.01 pM [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The core-shell beads' spherical configuration may offer an uncomplicated approach to concentrating and discerning light, thereby possibly further streamlining the optical system's design. Q. Lin et al further highlighted LAMP's adaptability for cancer-biomarker detection [162]. They introduced a dual-modality approach that integrates LAMP with magnetic bead isolation.…”
Section: (C) Precipitationmentioning
confidence: 99%
“…Reproduced with permission from Ref. [ 75 ]. (D) A CRISPR/Cas12a-based SNP detection genotyping method based on the centrifugal microfluidic device.…”
Section: Microfluidic Chip and On-chip Nucleic Acid Detectionmentioning
confidence: 99%
“…The determination of DNA methylation is still a challenge. Researchers have recently proposed a dual-mode LAMP incorporating magnetic bead separation to determine the methylated Septin9 gene in colorectal cancer [ 75 ]. A one-pot real-time fluorescent and colorimetric LAMP was used to detect the methylated Septin9 gene (60 min).…”
Section: Microfluidic Chip and On-chip Nucleic Acid Detectionmentioning
confidence: 99%